Role of Influencer Marketing in Building Brand Awareness - Kalkumbe, Khushi; Marathe, Amol; Longani, Kirti Dang (Universitas Muhammadiyah Sidoarjo, 2024)
This research paper explores the role of influencer marketing in building brand awareness, employing a quantitative approach through a Google Form questionnaire supplemented by existing literature reviews. The study aims to assess the effectiveness of influencer marketing in increasing brand recognition and to examine the relationship between influencer activities and brand visibility among target audiences. Findings from the survey reveal a significant correlation between influencer marketing efforts and heightened brand awareness, highlighting the pivotal role of influencers in shaping consumer perceptions and driving engagement. The rejection of the null hypothesis underscores the transformative potential of influencer collaborations as a core component of modern marketing strategies. Recommendations for businesses include prioritizing authenticity and alignment of values in influencer partnerships, along with implementing robust monitoring and evaluation mechanisms to optimize campaign effectiveness. Overall, this research underscores the importance of integrating influencer marketing into comprehensive brand promotion strategies to enhance visibility, engage with consumers authentically, and drive sustainable growth in today's competitive marketplace.